Characteristics of Ultramafik Rock and Nickel Laterite Distribution in Siuna Area, Pagimana, Banggai, Central Sulawesi: Karakteristik Batuan Ultramafik dan Penyebaran Nikel Laterit pada Daerah Siuna Kecamatan Pagimana Kabupaten Banggai, Sulawesi Tengah - Riska Puspita; Ninasafitri Ninasafitri; Moh. Rizal Ente (JURNAL GEOCELEBES, 2022)
The geology of Sulawesi Island, especially the eastern arm, is known to be composed of extensive ultramafic rocks with mineral deposit potential, including nickel laterite. The research area is located at PT. X Siuna, Pagimana District, Banggai Regency, Central Sulawesi Province. This study purpose to determine the characteristics of ultramafic rocks in the study area and to determine the distribution of laterite nickel and the relationship between ultramafik rock characteristics in the study area. The research methods used are field research methods and laboratory analysis (Petrography and XRF Analysis). Field research was conducted to collect field data in the form of rock samples and soil samples where there were 9 stations for rock samples and 4 stations for soil samples. Furthermore, laboratory analysis in the form of petrographic analysis will be carried out to determine the mineral composition of the rock, then XRF (X-Ray Flourescence) analysis is carried out to determine laterite nickel content which is then processed using ArcGIS 10.5 software, then interpolated using the Inverse Distance Weight (IDW) method. Based on the results of field and laboratory analysis, the rock characteristics in the study area have 3 rock types, namely serpentinized peridotite units, serpentinized dunite units and serpentinite units. The three rocks have been serpentinized with intermediate to strong  intensity, the constituent minerals have been dominated by serpentine, opaque mineral, pyroxine, and olivine. Based on IDW interpolation results, the distribution of nickel laterite in the western part of the study area has nickel (Ni) content of 0.50 – 1.2%, while in the southern – eastern part of the research area it has nickel (Ni) content of 0.20 – 0.5%